The Effect of Curcumin On Plasma Histamine Level, PEF Variation and Length of Stay of Patients With Acute Exacerbation Asthma - Lydia Arista Sutedjo; Suradi Suradi; Ana Rima Setijadi (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
Introduction: Inflammation in asthma occured in airway especially in submucous layer, and involve eosinophil, neutrophil, lymphocytes T, epitheliat cel, basophil, mast cell, and lymphocytes B. Inflammatory cells produce inflammatory mediators (histamine, leucotrienes, and prostanoid), cytokines, and chemokines that can cause bronchocontriction. This study was conducted to determine and prove the effect of curcumin as adjunctive therapy in acute exacerbation asthma. Curcumin is expected to increase the quality therapy of acute exacerbation asthma. The effect of curcumin is known wiith evaluate plasma histamine level, PEF variation, and length of stay of patient with acute exacerbation asthma. Methods: This study is a quasi experimental study with pretest and posttest design. Sampel of study is 30 patients hospitalizes acute exacerbation asthma in Moewardi hospital and Sohadi Prijonegoro Sragen hospital in August 2016 until september 2016. The subject was taken with concecutive random sampling. Independent variable is curcumin 4x550 mg and dependent variables are plasma histamin level, PEF variation, and length of stay. Result: There is no significant difference (P=0.462) of decreasing plasma histamine level between treatment group 3,988±2,739 ng/ml and control group 3,376±1,606 ng/ml. There is no significant difference (P=0.501) of PEF variation between treatment group 28,126±7,886% and control group 30,400±10,217%. There is no significant difference (P=0.936) of length of stay between treatment group perlakuan 6,333±2,193 days and control group 6,400±2,292 days. Conclusion: Giving curcumin in acute exacerbation asthma while hospitalized didn’t reduce inflammatory marker plasma histamin, PEF variation, and length of stay. (J Respir Indo 2018; 38(2): 100-8)